Hotspots and trends in fNIRS disease research: A bibliometric analysis - Ye, Xiangyin; Peng, Li; Sun, Ning; He, Lian; Yang, Xiuqiong; Zhou, Yuanfang; Xiong, Jian; Shen, Yuquan; Sun, Ruirui; Liang, Fanrong (Frontiers in Neuroscience, 2023)
Objective: To summarize the general information and hotspots of fNIRS-based clinical disease research over the past 10 years and provide some references for future research. Methods: The related literature published between January 1, 2011 and January 31, 2022 was retrieved from the Web of Science core database (WoS). Bibliometric visualization analysis of countries / regions, institutions, authors, journals, keywords and references were conducted by using CiteSpace 6.1.R3. Results: A total of 467 articles were included, and the annual number of articles published over nearly a decade showed an upward trend year-by-year. These articles mainly come from 39 countries/regions and 280 institutions. The representative country and institution were the United States and the University of Tubingen. We identified 266 authors, among which Andreas J Fallgatter and Ann-Christine Ehlis were the influential authors. Neuroimage was the most co-cited journal. The major topics in fNIRS disease research included activation, prefrontal cortex, working memory, cortex, and functional magnetic resonance imaging (fMRI). In recent years, the frontier topics were executive function, functional connectivity, performance, diagnosis, Alzheimer’s disease, children, and adolescents. Based on the burst of co-cited references, gait research has received much attention. Conclusion: This study conducted a comprehensive, objective, and visual analysis of publications, and revealed the status of relevant studies, hot topics, and trends concerning fNIRS disease research from 2011 to 2022. It is hoped that this work would help researchers to identify new perspectives on potential collaborators, important topics, and research frontiers.